1997
DOI: 10.1093/emboj/16.12.3599
|View full text |Cite
|
Sign up to set email alerts
|

High level transcription of a member of a repeated gene family confers dehydration tolerance to callus tissue of Craterostigma plantagineum

Abstract: An experimental system has been developed which allows the identification of intermediates in the abscisic acid (ABA) signal transduction pathway leading to desiccation tolerance in plants. Desiccation tolerance in callus of the resurrection plant Craterostigma plantagineum is mediated via the plant hormone ABA, which induces the expression of gene products related to desiccation tolerance. Based on T‐DNA activation tagging, a gene (CDT‐1) was isolated which encodes a signalling molecule in the ABA transductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 70 publications
1
110
0
Order By: Relevance
“…The expression of transgenes encoding stress-induced transcriptional factors or other components of stress-related signal transduction pathways (Table 2) might enable the coordinated upregulation of entire metabolic and/or signal transduction pathways affecting osmolyte levels in a developmentally, temporally and spatially controlled manner. The viability of this approach was recently shown by Furini et al (1997).…”
Section: Signal Transduction Mechanisms Regulating Osmolyte Accumulationmentioning
confidence: 96%
“…The expression of transgenes encoding stress-induced transcriptional factors or other components of stress-related signal transduction pathways (Table 2) might enable the coordinated upregulation of entire metabolic and/or signal transduction pathways affecting osmolyte levels in a developmentally, temporally and spatially controlled manner. The viability of this approach was recently shown by Furini et al (1997).…”
Section: Signal Transduction Mechanisms Regulating Osmolyte Accumulationmentioning
confidence: 96%
“…Analysis of RNA transcripts showed that genes were constitutively expressed in the mutant callus, which in non-transformed calli can only be induced by ABA treatment. The gene targeted by the T-DNA, which led to the constitutive activation of desiccation-related genes, was isolated and named CDT-1 (Furini et al, 1997). CDT-1 is present in multiple copies in the genome of C. plantagineum and its expression can be induced by ABA in nontransformed callus and plants.…”
Section: The Novel Cdt-1 Genementioning
confidence: 99%
“…This difference implies the existence of additional, unique protective mechanisms in the resurrection plants, a notion corroborated by the identification of the unusual eight-carbon sugar octulose, the CDT1 gene in Craterostigma plantagineum, and the phenolic antioxidant 3,4,5-tri-O-galloylquinic acid in Myrothamnus flabellifolia [12][13][14][15]. Furthermore, there is increasing evidence that some of the drought-protective mechanisms inducible in most plants by mild drought are constitutively active in resurrection plants [16,17].…”
Section: Introductionmentioning
confidence: 98%